2021
DOI: 10.17323/2587-814x.2021.2.75.90
|View full text |Cite
|
Sign up to set email alerts
|

How do information technology and knowledge management affect SMEs’ responsiveness to the coronavirus crisis?

Abstract: All organizations have been affected by the coronavirus pandemic in different ways. Small and medium-sized enterprises (SMEs) are more vulnerable to changes due to their limited resources. However, the capabilities of information technologies and processes of knowledge management can assist these enterprises to survive and respond appropriately to changes. Thus, this study aims to assess the extent to which information technology capabilities influence the responsiveness of SMEs to challenges that have emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Second, following literature, many MSMEs are adopting technology-associated solutions due to global crises such as the COVID-19 pandemic and worldwide lockdowns (Ali et al, 2021 ; Chowdhury et al, 2021 ). So, users on SM are talking more about different information technology (IT) solutions such as cloud-based infrastructures and video conferencing, which also impacts the buyer–supplier relationship (Azyabi, 2021 ). The current study on this literature expands the influence of MSMEs suppliers’ technological capability on the buyer experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, following literature, many MSMEs are adopting technology-associated solutions due to global crises such as the COVID-19 pandemic and worldwide lockdowns (Ali et al, 2021 ; Chowdhury et al, 2021 ). So, users on SM are talking more about different information technology (IT) solutions such as cloud-based infrastructures and video conferencing, which also impacts the buyer–supplier relationship (Azyabi, 2021 ). The current study on this literature expands the influence of MSMEs suppliers’ technological capability on the buyer experience.…”
Section: Discussionmentioning
confidence: 99%
“…Further resource dependency creates marred touchpoints for buyer experience, and on-time resource fulfillment may provide a positive experience for the suppliers. So, providing on-time resources when buyers are in crisis creates a positive synergy in the buyer–supplier relationship (Azyabi, 2021 ; Kurschus et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of publications recently could be attributed among other things to the Covid-19 pandemic and its effects, which may have led SMEs to invest more in KM in order to remain able to act during and after the pandemic. An example can be found in Azyabi’s ( 2021 ) study, which showed that the IT capabilities of SMEs are mediated by KM as a response to the disruption the Covid-19 pandemic caused. The struggles SMEs, in particular, had at the onset of the pandemic, given their limited resources, fueled debates around the topic, since many of them have been hit hard by the pandemic, which is also reflected in an increase in publications.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…By relating to the "organized" part of VRIO analysis developed by Barney (1995), it can be said that managerial competencies are critical for success, especially in crises that are highly volatile in their nature. In this sense, topics like stakeholder management including philanthropy, CSR, external communication, variety of stakeholders like migrants governments, civil society organizations (Al-Mansour and Al-Ajmi, 2020; He and Harris, 2020;Arslan, et al, 2021;Boeing and Wang, 2021;Bogomoletc and Lee, 2021;Chen, Liu, et al, 2021;Hammerschmidt, et al, 2021;He, et al, 2021;Kwok, et al, 2021;Lee and Li, 2021;Nayal, et al, 2021;Yen, et al, 2021) knowledge management (Iacuzzi, et al, 2020;Edghiem, et al, 2020;Ammirato, et al, 2020;Yigitcanlar, et al, 2021;Bratianu and Bejinaru, 2021;Saide and Sheng, 2021;Mariano, 2021;Klein and Todesco, 2021;Chen, Tansley and Chou, 2021;Azyabi, 2021), crisis management Hughes, et al, 2020;Kraus, et al, 2020;Moorkamp, et al, 2020;Lai and Wong, 2020;Alves, et al, 2020;Fasth, et al, 2021;Cullen and Murphy, 2021), governance (Kim, 2020;Ansell, et al, 2020;Sharma, Borah, and Moses, 2021;Abbas et al, 2021;Verbeke and Yuan, 2021), digitalization management (Anderson, 2020;Pūraitė, et al, 2020;Li, et al, 2020;…”
Section: Competenciesmentioning
confidence: 99%